How do private labels affect innovation in the food industry? - Glimvall, Sofia (2015)
There is a growing interest in private label products in the food industry and it has become an important strategy for food retailers to own and manage their own private label brands. Private labels have become a more popular topic to investigate, although so far, not much attention has been given towards the potential impacts private labels have on innovation. The focus of this thesis was therefore to analyze private label competition and the effects private labels have on innovation in the food industry. To approach this topic, an extensive literature review focusing on private labels, competition and innovation effect was performed. Empirical data was collected by interviews performed via the survey tool SurveyMonkey. In order to achieve a more in-depth data on the subject, two different surveys were distributed, one with relevant personnel from the food industry and one with experts from the academia. The key results in this thesis suggest that increases in private label shares could impede innovation within the food industry. The main reason for this is that private labels reduce the incentive for national brand manufacturers to invest resources in product development activities. The results from this thesis also imply that small manufacturers are especially vulnerable to increases in private label shares and that the development of "copycat" private labels could have a large negative effect on innovation in the food industry.